Phenolic, iridoid and ionyl glycosides from Homalium ceylanicum - Opinya A. Ekabo (2018)
Salireposide, salirepin and two related novel phenolic glycosides named homaloside B [1-(2-methoxybenzoyloxy)methyl-5-hydroxyphenyl-β-d- glucopyranoside] and homaloside C (1-furoyloxymethyl-5-hydroxyphenyl-β-d-glucopyranoside) were isolated from the n-butanol-soluble fraction of Homalium ceylanicum. Two other new glucosides, 6-O-(3″,4″-dimethoxycinnamoyl)catapol and 3-hydroxy-β-inoyl-β-d-glucopyranoside were also isolated from this fraction. The structures were solved by chemical and NMR spectroscopic (COLOC, FLOCK, selective INEPT) methods. © 1993.